Pelaporan, Pengelolaan, dan Pemanfaatan Aset Desa untuk Kesejahteraan Masyarakat Desa - Pratana Puspa Midiastuty; Eddy Suranta; Robinson Robinson; Rini Indriani; Danang Adi Putra; Mentari Gita Puspita (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to improve the understanding of village asset management, reporting, and utilization among officials in Tapak Gedung, Bengkulu, Indonesia. Conducted through a community service program, it involved training and mentoring to enhance officials' capacity to manage village assets according to legal regulations. The program included workshops, discussions, and feedback to assess participants' understanding of asset management and its role in community welfare. The study found significant improvements in participants' knowledge and skills, particularly in managing and reporting village assets like land and buildings. The findings highlight that training in asset management and reporting is essential for promoting transparency, accountability, and informed decision-making in village governance. However, challenges such as limited infrastructure and varying participant comprehension were encountered. The study emphasizes the need for continued support and capacity-building for sustainable asset management in village development. It is limited to one village and does not address challenges faced by others in Indonesia.